Matthew Arnold : The Poet as Humanist - Stange, G. Robert (George Robert), 1919-2007 (Book collections on Project MUSE., 1967)
Arnold is among the most inaccessible of 19th-century poets, a fact of which he himself was well aware. Asking a great deal of his readers, he expected them to share his remote excitements and to follow his complicated intellectual processes. This study of Arnold's major poetic ideas defines their philosophical backgrounds through close and sustained reading of many individual poems. Professor Stange finds that Arnold organized his examination of life around these central ideas: poetry, nature, self, and love. He also considers Arnold's work in relation to the philosophical and literary events and traditions of the continent, particularly Goethe's lyrics and classical humanism.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.